The Internal Determinants of the Market Value of Traditional Bank Shares Listed in the Damascus Securities Exchange (Econometric Study) (Journal of Hama University, 2026)
This research aims to test the effect of some internal determinants on the market value of traditional bank shares listed on the Damascus Stock Exchange during the period extending from (2011-2020). The sample included 11 traditional banks listed on the aforementioned market. Return on equity, earnings per share, bank size, and trading volume were chosen as independent variables, while the market value of the stock was the dependent variable and was measured through quarterly closing prices. The research relied on the real exchange rate and political stability as control variables.   To achieve the goal, the ARDL model methodology was used to test cointegration based on quarterly data of the PANEL type, after conducting unit root tests to ensure the stability of the variables. The results of the research showed a significant and positive effect of the trading volume, the real exchange rate and the size of the bank on the market value of the shares of the banks studied. While the effect was significant and negative for the return on equity and political stability, there was no effect of earnings per share on its market value in the long term. In the short term, it was found that there was a positive moral effect for earnings per share, return on equity, and political stability, while no effect was observed for bank size, trading volume, or real exchange rate on the market value of the shares of the banks studied.
Keywords: Internal Determinants, market value of the stock, Traditional banks, ARDL.